Potensi Tumbuhan Akuatik Hydrocotyle Sibthorpioides Lam sebagai Zat Antidiabetes Melitus Tipe 2 (T2D) - Putra, Aditya Pratama (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Type 2 diabetes mellitus is a condition of hyperglycemia caused by the insensitivity of cells to insulin even though insulin levels in the body are within the normal range. Hydrocotyle sibthorpioides Lam contains several important compounds, such as triterpenoid saponins, genin triterpenoids, essential oils, phytosterols, and flavonoids. This flavonoid compound is one of the potentially dominant compounds for people with type 2 diabetes mellitus. The purpose of writing this article is to determine the potential of the aquatic plant Hydrocotyle sibthorpioides Lam as an antidiabetic substance for type 2 diabetes mellitus (T2D). The research method used is a literature review with the number of articles used more than 10 journal articles. Flavonoids contained in the aquatic plant extract of Hydrocotyle sibthorpioides Lam have the potential as an antidiabetic drug by increasing insulin sensitivity in diabetics through its role in regulating insulin signaling mechanisms in target organs. Extracts from Hydrocotyle sibthorpioides Lam have great potential to be developed as an alternative treatment for type 2 diabetes mellitus (T2D). Further research and testing is needed regarding the effectiveness and side effects of this plant extract as a diabetes therapy.